2020
DOI: 10.3390/ani10071215
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Escherichia coli and ESBL-Producing Escherichia coli Diffusion in Conventional, Organic and Antibiotic-Free Meat Chickens at Slaughter

Abstract: As a result of public health concerns regarding antimicrobial resistance in animal-based food products, conventional poultry companies have turned to ‘raised without antibiotics’ (ABF) and organic farming systems. In this work, we evaluated the influence of rearing systems on antimicrobial susceptibility in E. coli and extended-spectrum β-lactamase (ESLB) E. coli diffusion in conventional (C), organic (O) and antibiotic free (ABF) chicken samples collected from cloacal swabs and skin samples in slaughterhouse.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
3
22
1
Order By: Relevance
“…*MAR isolates are those with resistance to at least two antibiotics [24] From this study, E. coli isolates were more resistant to streptomycin, sulphamethoxazole /trimethoprim, and ampicillin, which is similar to studies by [27], [31], and [32], but less resistant to imipenem, cefotaxime and ceftazidime. This finding is similar to a study by [33].The observed resistance of the E. coli from this study to commonly used antibiotics is not extraordinary as many studies worldwide have reported it [34,35] .…”
Section: Molecular Detection Of Extended-spectrum Beta-lactamase Genessupporting
confidence: 92%
“…*MAR isolates are those with resistance to at least two antibiotics [24] From this study, E. coli isolates were more resistant to streptomycin, sulphamethoxazole /trimethoprim, and ampicillin, which is similar to studies by [27], [31], and [32], but less resistant to imipenem, cefotaxime and ceftazidime. This finding is similar to a study by [33].The observed resistance of the E. coli from this study to commonly used antibiotics is not extraordinary as many studies worldwide have reported it [34,35] .…”
Section: Molecular Detection Of Extended-spectrum Beta-lactamase Genessupporting
confidence: 92%
“…Actually, Stedt et al [ 12 ] highlighted a south-to-north gradient in Europe (valid for E. coli from humans, food production animals and gulls), characterized by higher levels of resistance in Mediterranean countries and lower levels of resistance in northern Europe, with few local variations. These results, including ours, reflect the overuse of antibiotics in veterinary and human medicine over the years [ 12 , 14 ], and suggest that gulls might act as vectors but also as victims, acquiring resistant strains that potentially originate from humans or animals, which are often subjected to antibiotic administration [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 59%
“…On this matter it should be highlighted that in recent years most of the large Italian conventional poultry-producing companies have progressively turned to antibiotic-free and organic lines of products. However, in an our previous work [ 20 ] we found high prevalence of E. coli commensal strains resistant to tetracycline and nalidixic acid in both in antibiotic free and organic farming due likely to the vertical transmission and/or early contamination at hatch. Furthermore, an external environment contamination by resistant bacteria could be considered in an organic farm.…”
Section: Discussionmentioning
confidence: 72%